The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/imj.14027
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin delivers on convenience, cost reduction and clinical decision‐making in inflammatory bowel disease: a real‐world cohort study

Abstract: Introduction of FC into routine IBD care aided changes in clinical management in a similar proportion, yet at potentially half the total cost, compared to a historical colonoscopy-only cohort at the same centre. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In two studies, 12 out of 14 or 21 out of 34 positive FC values (≥ 250 μg/g) resulted in colonoscopies [26, 27]. In addition, Motaganahalli et al [11] showed that patients with positive FC (≥ 250 μg/mL) underwent colonoscopy earlier than patients with negative FC (< 100 μg/mL). However, none of these studies separated the CD from the UC cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In two studies, 12 out of 14 or 21 out of 34 positive FC values (≥ 250 μg/g) resulted in colonoscopies [26, 27]. In addition, Motaganahalli et al [11] showed that patients with positive FC (≥ 250 μg/mL) underwent colonoscopy earlier than patients with negative FC (< 100 μg/mL). However, none of these studies separated the CD from the UC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Local laboratory cut-off values were applied, with a result deemed ‘negative or normal’ if FC <50 mg/Kg, ‘positive’ if FC ≥50 mg/Kg and ‘definitely or highly positive’ if FC ≥250 mg/Kg. For this study, the cut-off value for FC was determined at 250 mg/Kg, as in other similar studies [11, 2428]. FC > 250 mg/Kg was considered a positive value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The state-of-the-art treatment goal for UC has shifted from clinical remission with symptom control to endoscopic remission using the treat-to-target strategy ( Jackson & De Cruz, 2019 ; Rubin et al, 2019 ; Wei et al, 2017 ). Fecal calprotectin (FC) is a non-invasive fecal marker commonly used in Western countries to determine mucosal healing ( Freeman et al, 2019 ; Motaganahalli et al, 2019 ); however, FC is expensive compared with the immune fecal occult blood test (iFOBT) and is not reimbursed for clinical use in Taiwan. By contrast, colonoscopy remains the gold standard for the assessment of colonic mucosal status, enables screening for colitis-associated malignancies ( Wei et al, 2017 ; Yen et al, 2017 ), and costs less in Asia than in Western countries ( Chang et al., 2020 ; Yen & Hsu, 2019 ).…”
Section: Introductionmentioning
confidence: 99%